Safety and physiological effects of two different doses of elosulfase alfa in patients with morquio a syndrome: A randomized, double‐blind, pilot study. (10th June 2015) - Burton, Barbara K.; Berger, Kenneth I.; Lewis, Gregory D.; Tarnopolsky, Mark; Treadwell, Marsha; Mitchell, John J.; Muschol, Nicole; Jones, Simon A.; Sutton, V. Reid; Pastores, Gregory M.; Lau, Heather; Sparkes, Rebecca; et al.
Abstract : The primary treatment outcomes of a phase 2, randomized, double‐blind, pilot study evaluating safety, physiological, and pharmacological effects of elosulfase alfa in patients with Morquio A syndrome are herewith presented. Patients aged ≥7 years and able to walk ≥200 m in the 6‐min walk test (6MWT) were randomized to elosulfase alfa 2.0 or 4.0 mg/kg/week for 27 weeks. The primary objective was to evaluate the safety of both doses. Secondary objectives were to evaluate effects on endurance (6MWT and 3‐min stair climb test [3MSCT]), exercise capacity (cardio‐pulmonary exercise test [CPET]), respiratory function, muscle strength, cardiac function, pain, and urine keratan sulfate (uKS) levels, and to determine pharmacokinetic parameters. Twenty‐five patients were enrolled (15 randomized to 2.0 mg/kg/week and 10 to 4.0 mg/kg/week). No new or unexpected safety signals were observed. After 24 weeks, there were no improvements versus baseline in the 6MWT, yet numerical improvements were seen in the 3MSCT with 4.0 mg/kg/week. uKS and pharmacokinetic data suggested no linear relationship over the 2.0–4.0 mg/kg dose range. Overall, an abnormal exercise capacity (evaluated in 10 and 5 patients in the 2.0 and 4.0 mg/kg/week groups, respectively), impaired muscle strength, and considerable pain were observed at baseline, and there were trends towards improvements in all domains after treatment. In conclusion, preliminary data of this small study in a Morquio A population with relatively good endurance confirmed the acceptable safety profile of elosulfase alfa and showed a trend of increased exercise capacity and muscle strength and decreased pain. © 2015 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.